Facial Affective Behavior in Borderline Personality Disorder Indicating Two Different Clusters and Their Influence on Inpatient Treatment Outcome: A Preliminary Study - Dammann, Gerhard; Rudaz, Myriam; Benecke, Cord; Riemenschneider, Anke; Walter, Marc; Pfaltz, Monique C.; Küchenhoff, Joachim; Clarkin, John F.; Gremaud-Heitz, Daniela J. (Frontiers in Psychology, 2020)
Background: The purpose of the present study was to investigate whether patients with a Borderline Personality Disorder (BPD) could be divided into clusters according to facial affective behavior and whether these clusters would influence the inpatient treatment outcome. Methods: 30 inpatients with BPD were assessed with the Structured Clinical Interviews for DSM-IV Axis I and II Disorders (SCID I, SCID II) and had to complete a series of questionnaires before and directly after the 12-week long inpatient treatment. Facial affective behavior was recorded during the Structured Interview for Personality Organization (STIPO) and afterwards coded with the Emotional Facial Coding System (EMFACS). Measures on psychopathology (Beck Depression Inventory/BDI, Spielberger State and Trait Anxiety Inventory/STAI, Spielberger State and Trait Anger Inventory/STAXI, and Symptom Cheklist-90-Revised/SCL-90-R), interpersonal problems (Inventory of Interpersonal Problems/IIP), and personality organization (Inventory of Personality Organization/IPO) were administered. Results: Cluster analysis before the treatment yielded two different groups which were characterized by the general amount of facial activity as well as the basic emotions. The effect sizes of the repeated measures ANOVAs showed that persons with higher scores on the affective facial expressions benefitted more from the treatment in terms of STAI state anxiety, STAXI state and trait anger, IIP total and the two scales primitive defenses and identity diffusion of the IPO, whereas persons with lower scores benefitted more on the scale IPO reality testing. Conclusions: Our results indicated some initial trends for the importance of facial affective behavior in patients with BPD and their treatment outcome.